The Role of Artificial Intelligence in Predicting Mortality Risk of Transcatheter Aortic Valve Replacement: A Systematic Review - Arasyi, Hidtsa Aqila Noor; Arasyi, Firqa Aqila Noor; Pratama, Rizky (Universitas Airlangga, 2024)
Highlights: 1. Understanding how Artificial Intelligence could play a crucial role in diagnosing patients’ mortality could be challenging, however, this article could provide a discussion that readers might want to take notice. - Background: Artificial intelligence plays a crucial role in the field of cardiovascular medicine, particularly in diagnosing and predicting patient mortality in heart disease. Objective: Therefore, we conducted a systematic review to understand the role of artificial intelligence in predicting mortality risk in patients with aortic stenosis following transcatheter aortic valve replacement (TAVR). Method: This study is a systematic review using secondary data. The data in this research consist of literature on the role of artificial intelligence in TAVR patients, obtained through the PubMed, ScienceDirect, and Google Scholar search engines, with a publication date range from 2019 to October 2023. Using the PRISMA flow diagram, six studies on the role of artificial intelligence in TAVR patients were identified. It was found that the ability of artificial intelligence to predict mortality in patients with aortic stenosis undergoing Transcatheter Aortic Valve Replacement (TAVR) is superior compared to the TAVI2-Score, CoreValve Score, STS/ACC Score, and several other prediction scores. Conclusion: Artificial intelligence has a superior ability to predict mortality risk in patients with aortic stenosis undergoing Transcatheter Aortic Valve Replacement (TAVR).